2021
DOI: 10.1177/1535370220981578
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-based delivery of interleukin-9 to neovascular structures: Therapeutic evaluation in cancer and arthritis

Abstract: Interleukin-9 is a cytokine with multiple functions, including the ability to activate group 2 innate lymphoid cells, which has been postulated to be therapeutically active in mouse models of arthritis. Similarly, interleukin-9 has been suggested to play an important role in tumor immunity. Here, we describe the cloning, expression, and characterization of three fusion proteins based on murine interleukin-9 and the F8 antibody, specific to the alternatively spliced EDA domain of fibronectin. EDA is strongly ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…In a preclinical model of monocrotaline (MCT)‐induced PH in mice, we observed advantageous effects in terms of attenuation of both, PAP and right ventricular load 29 . Besides this, the immunocytokine could be proven to mediate beneficial effects in murine models of melanoma and colon cancer 29,30 …”
Section: Introductionmentioning
confidence: 97%
“…In a preclinical model of monocrotaline (MCT)‐induced PH in mice, we observed advantageous effects in terms of attenuation of both, PAP and right ventricular load 29 . Besides this, the immunocytokine could be proven to mediate beneficial effects in murine models of melanoma and colon cancer 29,30 …”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, IL-9 administration in mice using a gene therapy approach was associated with the resolution of inflammation and disease progression [ 49 ]. However, contradictory results were obtained in a study performed by Gouyou et al [ 50 ]. In this study a therapeutic benefit was not observed in arthritis mice after delivering IL-9-based fusion proteins.…”
Section: Discussionmentioning
confidence: 94%